USING MOBILE APPS FOR DEVELOPING VOCABULARY COMPETENCE - Khodjaniyazova, Umida (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
Incorporating multimedia program-based tasks into vocabulary instruction represents a contemporary and effective pedagogical approach that capitalizes on the interactive nature of digital resources. This article aims to describe both the theoretical and practical aspects of the mobile app “Word Case,” which is an innovative multimedia program designed to enhance the vocabulary competence of B1-level learners of English. “Word Case” offers a diverse range of multimedia resources, such as interactive games and audio recordings, catering to various learning styles and preferences. This diversity ensures that students are exposed to vocabulary in different contexts and formats, enhancing comprehension and retention. The program provides opportunities for autonomous learning, empowering students to explore and practice vocabulary at their own pace and according to their individual interests. Moreover, “Word case” facilitates continuous assessment and feedback, enabling teachers to monitor student progress and tailor instruction accordingly. The study analyzes various viewpoints on the “Multimedia program” as considered by scholars of philosophy, psychology, and pedagogy, and describes the results of a questionnaire.